Interest Rate Spreads in English-Speaking African Countries - Crowley, Joe. (Washington, D.C. : International Monetary Fund, 2007)
This paper examines interest rate spreads in English-speaking African countries. Higher spreads were found to be associated with lower inflation, a greater number of banks, and greater public ownership of banks. Higher deposit interest rates were found to be associated with lower interest rate spreads, but higher net interest margins. A large increase in spreads in the late 1980s and 1990s may be explained by a strengthening of financial sector supervision. Limited data suggested that poor governance, weak regulatory frameworks and property rights, and higher required reserve ratios are associated with higher spreads.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet